The influence of habitat structure, at different spatial scales, on the ecological distribution of macroalgal communities in streams - Krupek, Rogerio Antonio; Zanini Branco, Ciro Cesar [UNESP] (Soc Botanica Sao Paulo, 2016)
Habitat heterogeneity influences the composition and structure of macroalgal communities in lotic environments. However, depending on the spatial scale, different environmental characteristics may exert more or less influence. This study aimed to evaluate, at different spatial scales of observation, the influences of local and regional environmental variables on ecological distribution of macroalgae in stream ecosystems. The field work was conducted during the months of June and July 2007 in streams of two river basins located in southern Brazil. The spatial scales used were drainage basin, shading, mesohabitat, and microhabitat. According to the results, there are few differences regarding abiotic variables between spatial scales, however, suggesting that sunlight and, consequently, the shading scale have a strong impact on the distribution pattern of stream macroalgae. The mesohabitat scale at the current velocity proved to be an important factor in structuring communities of macroalgae. Finally, microenvironmental factors (e.g., substrate, current velocity, and light availability) appear to exert their direct influence on the spatial distribution of stream macroalgae, generating particular features in each spatial scale of observation, although regional abiotic parameters (e.g., temperature, pH, and conductivity) should also be considered for the structural characterization of these organisms.
Keywords: Heterogeneity; Macroalgae; Microhabitat; Stream